Caracterização dos Componentes da Fração Arenosa(0,500mm/0,250mm) no Canal de São Sebastião (SP) - BARCELLOS, ROBERTO; FURTADO, VALDENIR VERONESE (Pesquisas em Geociências, 2001)
The present study investigates the sedimentary dynamics and evaluates the terrigenous or marine inputs to the sediments of São Sebastião Channel (SP), Brazil, through the utilization of sand fraction analysis. Results show, for the summer and winter, in the granulometric fractions of 1Ø and 2 Ø, a decrease of marine contribution from the south to the north of the channel, and from the island side to the continental side. The greater terrigenous influence in the northern portion and in the continental side of the channel is related to lower depths, lower hydrodynamics and the small influence of the shelf water masses. The greater marine influence occurs within the higher depths of the channel axis. This influence is related to shelf water masses penetration through the channel south mouth, increasing the input of marine originated material. The utilization of sand fraction analysis for the São Sebastião Channel sediments is a good tool to identify the type of inputs for the sediments. This technique also complements the interpretations of another parameters, such as grain size geochemical data, allowing a detailed evaluation of sedimentary processes that acts in the study area.